Lion dancer : Ernie Wan's Chinese New Year - Waters, Kate.; Slovenz-Low, Madeline; Cooper, Martha (New York : Scholastic Inc., 1990)
Describes six-year-old Ernie Wong's preparations, at home and in school, for the Chinese New Year celebrations and his first public performance of the lion dance.
G3
Keywords: Chinese New Year -- New York (State) -- New York -- Juvenile literature; Chinese New Year -- New York (State) -- New York; Chinese Americans; Chinatown (New York, N.Y.) -- Social life and customs -- Juvenile literature; New York (N.Y.) -- Social life and customs -- Juvenile literature; Chinatown (New York, N.Y.) -- Social life and customs